Associations between oral HPV16 infection and cytopathology: evaluation of an oropharyngeal “Pap-test equivalent” in high-risk populations - Fakhry, Carole (2011)
Human papillomavirus (HPV) is responsible for the rising incidence of oropharyngeal squamous cell cancers (OSCC) in the United States (U.S.), and yet, no screening strategies have been evaluated. Secondary prevention by means of HPV detection and cervical cytology has led to a decline in cervical cancer incidence in the U.S. Here, we explored an analogous strategy by evaluating associations between HPV16 infection, cytopathology and histopathology in two populations at elevated risk for OSCC. In the first, a cross-sectional study population (PAP1), cytology specimens were collected by means of brush biopsy from patients presenting with oropharyngeal abnormalities. In the second (PAP2), a nested case-control study, bilateral tonsillar cytology samples were collected at 12-month intervals from HIV-infected individuals. The presence of cytopathological abnormality in HPV16-positive tonsil brush biopsies (cases) was compared to HPV16-negative samples (controls) matched on age and gender. HPV16 was detected in samples by consensus primer PCR and/or type-specific PCR. Univariate logistic regression was used to evaluate associations. In PAP1, HPV16 alone (OR 6.1, 95%CI 1.6–22.7) or in combination with abnormal cytology (OR 20, 95%CI 4.2–95.4) was associated with OSCC. In PAP2, 4.7% (72 of 1524) of tonsillar cytology specimens from HIV-infected individuals without oropharyngeal abnormalities were HPV16-positive. Tonsillar HPV16 infection was not associated with atypical squamous cells of unknown significance (ASCUS), the only cytological abnormality identified. Therefore, HPV16 was associated with OSCC among individuals with accessible oropharyngeal lesions, but not with cytological evidence of dysplasia among high-risk individuals without such lesions. An oropharyngeal Pap-test equivalent may not be feasible, likely due to limitations in sampling the relevant tonsillar crypt epithelium.